2001
DOI: 10.1002/gene.10014
|View full text |Cite
|
Sign up to set email alerts
|

Cre‐mediated transgene activation in the developing and adult mouse brain

Abstract: The neuron-specific rat enolase (NSE) promoter was employed to establish transgenic mice expressing Cre recombinase in the central nervous system. Founders were crossed with dormant lacZ indicator mice and specificity as well as efficiency of Cre-mediated transgene activation was determined by PCR and/or X-gal staining. Whereas most transgenic lines exhibited Cre activity in early development resulting in widespread Cre activity, one line (NSE-Cre26) expressed high levels of Cre in the developing and adult bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
(28 reference statements)
4
19
0
Order By: Relevance
“…4). As previously described in other Nse transgenic mice (Cinato et al, 2001;Forss-Petter et al, 1990), we also observed some transgene activity in the kidney and testes from the Nse-cre CK2 line (Fig. 4g,h).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…4). As previously described in other Nse transgenic mice (Cinato et al, 2001;Forss-Petter et al, 1990), we also observed some transgene activity in the kidney and testes from the Nse-cre CK2 line (Fig. 4g,h).…”
supporting
confidence: 76%
“…When analyzed by X-gal staining or immunostaining for b-galactosidase, the Nse-cre CK1 ; Rosa26R line showed cre activity in developing nervous system and most mature neurons of the brain (data not shown), which is similar to the ac-tivity of previously reported Nse transgenic lines (Cinato et al, 2001;Forss-Petter et al, 1990). In contrast, the Nse-cre CK2 ; Rosa26R line exhibited a distinct pattern of cre activity, as described below.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Unlike other gene promoters, the hGFAP promoter is active not only in neural stem cells and most neurons but also in glial cells (astrocytes) (Zhuo et al, 2001). Among all pro-moter genes described in CNS, only the neuron-specific rat enolase (NSE) was reported as a pan-neuronal expressor in the developing and adult mouse brain (Cinato et al, 2001). Thus, the pan-neuronal seen in the MLC2v-Cre3 transgenic mouse line provides a useful tool to specifically inactivate genes throughout neurons of the developing and adult mouse brain and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral deficits of AR null mice could in principle result from a disruption of AR signaling in the pituitary or from a lack of AR signaling in the brain. Using the Cre-lox system, brain-specific deletions of AR can be generated with the available Cre and floxed AR lines (Figure 3a) (Cinato et al, 2001;Goebbels et al, 2006;Korets-Smith et al, 2004;Tronche et al, 1999;Tsien et al, 1996;Zhu et al, 2001). Deficits in either mating or aggression in such mice would provide a convincing demonstration of a neural requirement of AR in these behavioral routines.…”
Section: Spatially Restricted Manipulation Of Ar Functionmentioning
confidence: 99%